Kualitas Audit Dan Faktor-Faktor Yang Mempengaruhinya(Studi Empiris Pada Kantor Akuntan Publik Wilayah Jateng Dan Diy) - Fatimah, Isnaini Fitri, Drs. Muhammad Abdul Aris, M.Si (2016)
This study aims to analyze and obtain empirical evidience about the effect of competence, independence, work experience, due profesional care, and accountability of auditors on audit quality auditors owned Public Accounting Firm in Jawa Tengah and DIY. This research was conducted using a survey method with a questionnaire. This study uses primary data obtained by distributing questionnaire to 59 respondents. Data analysis was performed with multiple linier regression method. This study found that competence, independence, work experience, professional due care and accountability of auditors have a significant positive effect on audit quality.